Human origin of Bacteroides fragilis bacteriophages present in the environment. - Tartera, C (1989)
Bacteroides fragilis HSP40 phages have been detected in waters with various levels of fecal contamination of human origin. The average numbers of B. fragilis phages present in sewage water reached 5.3 x 10(3) per 100 ml of water. We found a number 1,000 times lower in a river contaminated with domestic sewage only, in which the levels of fecal coliforms and fecal streptococci were 10,000 times lower than those found in raw sewage. In addition, B. fragilis phages were not found in significant numbers in slaughterhouse wastewaters. They were not present in fecal-polluted waters containing fecal contamination from wildlife only. Although the number of B. fragilis phages present in contaminated waters was lower than the number of coliphages, their presence indicated human fecal contamination. It is also shown that Bacteroides phages are only able to multiply under anaerobic conditions in the presence of nutrients, and they cannot multiply in natural waters and sediments.